2022
DOI: 10.3390/nano12193338
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible and Robust Structural Color Film Obtained by Assembly of Surface-Modified Melanin Particles

Abstract: In this study, core–shell-hairy-type melanin particles surface modified with a polydopamine shell layer and a polymer brush hairy layer were fabricated and assembled to readily obtain bright structural color films. The hot pressing of freeze-dried samples of melanin particles decorated with a hydrophilic, low glass transition temperature polymer brush results in films that exhibit an angle-dependent structural color due to a highly periodic microstructure, with increased regularity in the arrangement of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Recently, several strategies have been reported for improving the mechanical robustness of particle-array-type structurally colored materials. [25][26][27][28][29] The addition of polymers-such as poly(vinyl alcohol), [25] polyacrylate, [26,28] and polydopamine [29][30][31] -as binders is a typical approach to enhance the mechanical durability of particle arrays. For example, Xing et al demonstrated that structurally colored fabrics prepared using polydopamine-coated spheres have bright structural colors, strong mechanical robustness, and can withstand soaking, laundering, folding, and abrasion testing.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several strategies have been reported for improving the mechanical robustness of particle-array-type structurally colored materials. [25][26][27][28][29] The addition of polymers-such as poly(vinyl alcohol), [25] polyacrylate, [26,28] and polydopamine [29][30][31] -as binders is a typical approach to enhance the mechanical durability of particle arrays. For example, Xing et al demonstrated that structurally colored fabrics prepared using polydopamine-coated spheres have bright structural colors, strong mechanical robustness, and can withstand soaking, laundering, folding, and abrasion testing.…”
Section: Introductionmentioning
confidence: 99%
“…Photonic crystals (PCs) are a class of materials that are promising both for studying new fundamental phenomena in quantum and nonlinear optics and for creating hierarchical materials with new physical, physicochemical, or biological properties. The fundamental property of PCs is a spatially periodic change of its permittivity with a period comparable to the light wavelength. Since the reflection wavelength of a polymer film based on PCs can be easily varied by changing the diameter of monodisperse polymer particles, it is possible to create optical sensor materials based on polymeric PCs. Also, the reflection wavelength of the PC-based film can be modulated by changing the lattice spacing due to external influences, such as temperature, pressure, and the presence of volatile organic compounds. PCs with tunable optical properties have great potential for a wide range of applications such as strain sensors or smart labels. …”
Section: Introductionmentioning
confidence: 99%
“…Based on the coloration mechanisms of vivid organisms involving microstructures formed by melanin, a biopolymer that absorbs visible light, , we conducted a series of studies on biomimetic structural color materials containing polydopamine (PDA), a melanin-mimetic substance. , Due to incoherent multiple scattering, conventional materials produce whitish structural colors and low saturation. On the other hand, melanin particles, i.e., PSt@PDA core–shell particles with PDA coated on the surfaces of monodisperse polystyrene (PSt) particles, produce a variety of highly visible structural colors depending on their sizes, shapes, and compositions. Coating the particle surface with PDA can absorb light in the visible region and suppress diffuse reflection, thereby improving structural color contrast, which can be achieved using carbon-based materials as well . The use of melanin particles as building blocks is an effective way to produce vivid structural color materials. , Thus, developing crack-free melanin-based structural color materials remains an attractive challenge for practical application.…”
Section: Introductionmentioning
confidence: 99%